The progress achieved by judokas after strength training with a judo-specific machine - Blais, L.; Trilles, F. (Journal of Sports Science & Medicine, 2006)
For judo players, as in many sports activities, strength development has become an important element of performance. However, this should not be done separately from the development of technique. Specific strength training is thus used for the controlled strengthening of specific muscles or muscle groups, corresponding to the movement in a competitive situation. In line with this, the use of a judo specific apparatus is proposed. The aim of this study is to analyze the progress of a group of judokas after a training program with the apparatus. The results have shown that, using the apparatus, the heaviest weight achieved using the throwing technique is greater. In addition, the judokas` technique improves as a consequence of this training program. This judo specific apparatus could therefore be used to complement traditional judo training.